Investigations of asymmetric non-premixed meso-scale vortex combustion - Khaleghi, Mostafa (Elsevier, 2015)
A new design of asymmetric non-premixed meso-scale vortex combustor is introduced in this paper. The flame stability, heat loss from the combustor wall as well as thermal efficiency and pollutant formation are compared in various circumstances such as air/fuel inlet velocity and equivalence ratios. Furthermore, direct photography method is used to capture visible flame structures at a wide range of equivalence ratios in order to emphasize the exceptional stability of such flames. An essential model for the stability of non-premixed flames in meso-scale combustion spaces is provided in this research. The temperature of the combustor wall is one of the most important factors that influence the temperature of the reactants (preheating phenomena) by heat conduction through the body. The results show that in the stoichiometric circumstance, when air mass flow rate is at the lowest rate (40 mg/s), the ratio of heat loss to heat generation reaches the largest value (around 55%). The average temperature of the combustor wall increases with the flow velocity for the stable flame mode and remains mostly uniform and well distributed for the vortex flame in toroidal shape. At a constant airflow rates, the exhaust temperature increases monotonously with the decrease in equivalence ratio until the flame blows off. This implies that the maximum thermal efficiency of a meso-scale combustor occurs in its lean conditions